Massive Open Online Course Versus Flipped Instruction: Impacts on Foreign Language Speaking Anxiety, Foreign Language Learning Motivation, and Learning Attitude - Pan, Hui; Xia, Fang; Kumar, Tribhuwan; Li, Xiang; Shamsy, Atefeh (Frontiers in Psychology, 2022)
This study inspected the effect of Massive Open Online Course (MOOC) and flipped instruction on EFL learners’ foreign language speaking anxiety, foreign language learning motivation, and attitude toward English learning. To fulfill this objective, the Oxford Quick Placement Test (OQPT) was given to 160 Iranian EFL learners, of whom 120 upper-intermediate participants were chosen and divided into two experimental groups- MOOC (n = 40) and flipped (n = 40)- and one control group (n = 40). After that, all selected participants were administered a speaking anxiety questionnaire and a motivation questionnaire as the pretest of the research. Then, one of the experimental groups received an online-based instruction via Skype: one conversation was instructed to this group online every session. The other experimental group received the treatment via flipped-based instruction. The audio files and the texts of the conversations were sent to this group via the WhatsApp application because they all had easy access to it. On the other hand, the control group did not receive any Internet-delivered treatment yet was trained through a face-to-face method. This process continued until the last session, and after the treatment period, the post-tests of speaking anxiety and motivation were given to all three groups to determine the effectiveness of the treatment. Moreover, two attitude questionnaires were administered to the experimental groups to examine their attitudes toward the MOOC and the flipped models of instructions. The findings of the One-way ANOVA test, Post-hoc Scheffe test, and paired samples t-test showed that there were significant differences between the post-test of the experimental groups and the control group. The results indicated that the experimental groups significantly outflanked the control group after the treatment. Lastly, the outcomes showed that participants in both experimental groups had positive attitudes toward technological-based instructional environments.